PENERAPAN RELAKSASI AUTOGENIK UNTUK MENURUNKAN NYERI KEPALA PADA NY.A DENGAN HIPERTENSI DI RSUD ARIFIN ACHMAD - Muhammad Nurman; Dody alkadri Halijur (Jurnal Spektrum Kesehatan Indonesia, 2025)
The increasing prevalence of elderly people has led to various changes that impact health problems, such as decreased heart function, one of which is hypertension. Hypertension is a circulatory system disorder that can cause blood pressure to rise above normal values, namely systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg. One symptom of hypertension that interferes with activities is headache at the back of the head, dizziness, discomfort in the neck area, and blurred vision. Non-pharmacological therapy that can be given to hypertension sufferers is autogenic relaxation therapy. Based on observations of real conditions in the field, it was seen that in hypertensive patients, I was found to have acute headache problems. The treatment to overcome headaches is autogenic relaxation therapy. The results of the study showed that with autogenic relaxation therapy, the pain scale decreased and then the blood pressure of the researchers observed decreased from 160/90 mmHg to 140/90 mmHg. It is hoped that the patient's family can use autogenic relaxation techniques on patients if the patient experiences headaches due to hypertension.